Can Polyhydroxyalkanoates Be Produced Efficiently From Waste Plant and Animal Oils? - Surendran, Arthy; Lakshmanan, Manoj; Chee, Jiun Yee; Sulaiman, Azlinah Mohd; Thuoc, Doan Van; Sudesh, Kumar (Frontiers in Bioengineering and Biotechnology, 2020)
Polyhydroxyalkanoates (PHA) are a potential next generation material to replace some of the petrochemical based plastics. PHAs are polyesters synthesized and stored by various prokaryotes and archaea as water-insoluble inclusions in their cytoplasm. PHAs are usually produced when the microbes are cultured in nutrient limiting conditions with excess carbon sources. Hence this concept is implemented in industries to reduce cost of PHAs produced commercially. Industrially, these biodegradable polyesters are derived from microbial fermentation processes by utilizing various carbon sources. One of the major constraints in scaling-up of the PHA production is the cost of the carbon source used by the microorganisms. Hence, cheap and renewable carbon substrates are currently being investigated around the globe. Plant and animal oils have been demonstrated to be excellent carbon sources for the high-yield of PHAs. Waste streams from oil mills or the used oils, which are even cheaper than the oils, are also used. This approach not only reduces the production cost for PHAs, but also makes a significant contribution towards the reduction of environmental pollution caused by the used oil. Advancements in the genetic and metabolic engineering of bacterial strains have enabled a more efficient utilization of various carbon sources, in producing high PHA yield with various monomer compositions. Hence this review attempts to discuss recent developments in the biosynthesis and classification of various forms of PHAs produced using crude and waste oils from the oil palm and fish industries. Besides that, the biodegradability of the PHAs produced from these oils will also be discussed.